The Implementation of an Ethno-Inquiry-Based Science Module to Enhance the Scientific Process Skills of Prospective Primary School Teachers - Oviana, Wati; Jannah, Misbahul; Nurdin, Syahidan; Rahmi, Putri (Universitas Islam Negeri Raden Intan Lampung, 2025)
This study examines the effectiveness of an ethno-inquiry-based science module in enhancing the scientific process skills of prospective primary school teachers. Science education at the tertiary level often lacks cultural context, which limits student engagement and skill development. Employing a quasi-experimental pretest-posttest control group design, 50 students from the Islamic Primary Education program at UIN Ar-Raniry were randomly assigned to control and experimental groups. The module integrated local cultural practices with inquiry-based learning, targeting six core scientific process skills: observing, inferring, measuring, classifying, predicting, and communicating. Data were collected through validated assessments and student response questionnaires. The results revealed that the experimental group achieved a moderate n-Gain of 0.36, compared to 0.06 in the control group. Students rated the module highly, with 86% finding it particularly relevant and engaging. These findings suggest that incorporating local knowledge into science instruction significantly enhances both cognitive and cultural learning outcomes. The study underscores the potential of ethno-inquiry-based approaches in fostering scientific skills while preserving cultural identity in teacher education.